Protocol for a 20-year follow-up after a randomized controlled trial of a Mediterranean diet in pregnancy: maternal and offspring risk factors for cardiovascular disease - Hannibal Troensegaard; Janette Khoury; Ane C. Westerberg; Ane C. Westerberg; Serena Tonstad; Jeanine Roeters van Lennep; Marit B. Veierød; Per Ole Iversen; Per Ole Iversen; Kirsten B. Holven; Kirsten B. Holven; Kjetil Retterstøl; et al. (Frontiers Media S.A., 2023)
BackgroundAn inadequate maternal diet during pregnancy can impair offspring health and may increase the risk of cardiovascular disease later in life. The purpose of the proposed study is to assess the risk factors associated with cardiovascular disease in both mothers and their offspring 20 years following their participation in a Mediterranean diet intervention trial during pregnancy.MethodsThe "Cardiovascular Risk Reduction Diet In Pregnancy" (CARRDIP) study was a randomized controlled trial performed between 1999 and 2001. The participants were randomized to adhere to either a Mediterranean diet or their regular diet during pregnancy. An extensive amount of data such as diet information, ultrasound measurements, anthropometry, and biomarkers from these mothers during pregnancy and their offspring in the neonatal period were collected. The mother-offspring pairs (n = 269) from the CARRDIP study will be invited to participate in a clinical examination and blood sample collection. This follow-up study, conducted 20 years after the original CARRDIP study, will investigate cardiovascular risk factors in mothers and offspring. The primary outcome will be the blood pressure of the offspring. In addition, the study will explore various aspects of cardiovascular health, including metabolic and inflammatory status, clinical history, and body composition of the participants.DiscussionPrevious studies investigating the effects of nutrition during pregnancy on maternal and offspring health have been either observational studies, animal studies, or randomized controlled trials with a follow-up period of less than 5 years. This project aims to study the long-term effects of dietary intervention during pregnancy on maternal and offspring cardiovascular risk markers.Clinical Trial RegistrationClinicaltrials.gov, identifier (NCT05030922).